PERANCANGAN REDESAIN PACKAGING PEYEK DAUN KOPI SARTIKA - Robby Usman; Maulia Fathia (Iam-Indonesia, 2023)
ABSTRACT Kerinci Regency is one of the coffee producing districts in Indonesia. One of the processed products of the coffee plant is peyek coffee leaves made from coffee leaves. Coffee leaf peyek food is a unique type of food. With the uniqueness that exists, but it is very unfortunate that coffee leaf peyek does not yet have an attractive packaging form. So that the lack of knowledge and public interest in the product Peyek Daun Kopi Sartika. Peyek daun kopi sartika is a superior product from the industrial house Sartika Kerinci. Therefore, it is very unfortunate if the packaging of sartika coffee leaf peyek is not updated. The designer took the object of peyek daun kopi sartika because he saw the magnitude of the opportunity of the product to develop and compete in the market. Designers find design solutions using primary, secondary and tertiary packaging. Keywords : Packaging, Design, Food, Peyek Leaf Coffee